Endotoxin Increases Ascorbate Recycling and Concentration in Mouse Liver - Kuo, Shiu-Ming (2005)
Sublethal exposure to Escherichia coli endotoxin (lipopolysaccharide, LPS) attenuates the lethal effects of subsequent insults associated with oxidative stress, such as higher LPS dose, septic peritonitis and ischemia. Because administration of the antioxidant ascorbate protects against these same insults and injection of dehydroascorbic acid (DHAA) protects against ischemia, the hypothesis that sublethal LPS increases endogenous ascorbate concentration and recycling (i.e. synthesis from DHAA) was tested. Injection of LPS (5 × 10(6) EU/kg body weight i.p.) in mice caused a temporary inhibition of food intake, which was significant by 20 h and recovered within 3 days. LPS increased ascorbate concentration in adrenal gland, heart, kidney and liver. LPS had similar effects in wild-type and Slc23a2+/− mice despite the latter’s deficiency in the ascorbate transporter SVCT2. In liver, the ascorbate response to LPS was not accompanied by change in glutathione concentration. LPS decreased gulonolactone oxidase activity, which is rate-limiting for de novo synthesis of ascorbate from glucose, but increased the rate of DHAA reduction to ascorbate. In conclusion, sublethal endotoxin increases ascorbate recycling in liver and ascorbate concentration in liver, adrenal gland, heart and kidney. The enhanced rate of ascorbate production from DHAA may protect these organs against the reactive oxygen species produced by subsequent, potentially lethal challenges.